Power distance and its moderating role in the relationship between situational job characteristics and job satisfaction: An empirical analysis using different cultural measures. Issue 1 (2nd February 2015) - Hauff, Sven; Richter, Nicole
Abstract : Purpose: – Power distance describes a central facet of national culture, because it influences the acceptance and endorsement of job characteristics related to status and power. This has major implications for international human resource management, because the importance of different situational job characteristics for employee job satisfaction should differ across cultures. The purpose of this paper is to analyse if and how national power distance levels moderate different situational job characteristics' influence on job satisfaction. Design/methodology/approach: – The authors refer to three approaches to culture: the frameworks of Hofstede and GLOBE as well as to current scores provided in a meta-analysis. The empirical findings are derived using regression analyses on a sample covering 16 nations. Findings: – The results are convincing regarding the basic job satisfaction driver model not involving culture. However, the results on power distance's impact as well as its moderating role are strongly dependent on the culture concepts utilised. The authors provide an analysis of differences along the measurements behind the different concepts. Originality/value: – The authors can conclude that national differences in job satisfaction, as found in various studies, are a result of differences in situational dispositions to work life rather than a result of different cultural surroundings in terms of power distance. The question is whether this is due to power distance's lack of impact or due to other factors, such as the difficulties of measuring culture. The authors discuss the differences which are due to different measurements. For ultimately confirming power distance's moderating role and for advancing theorizing in this field, further research, which can build on the framework offered in this paper, is needed that directly measures the individual power distance facets in addition to the job characteristics and satisfaction values.